Exploring The Depth Of Figurative Language And Its Meanings In Eminem's 'Kamikaze' Album: A Comprehensive Analysis - Mohamad Arif Hamidi; Agustinus Hary Setyawan (Departement of Mathematics Education, 2024)
This study examines the figurative language techniques employed in the Kamikaze album by Eminem using Perrine's theoretical framework for figurative language qualitative descriptive research method. A total of 321 instances of figurative language were identified, with symbolism emerging as the most prevalent device (34 occurrences), while apostrophe was the least utilized (18 occurrences). Symbolism, chosen for its ability to convey abstract concepts and emotions through vivid imagery, allows Eminem to intricately weave personal narratives with societal critiques. Through allegory, metaphor, personification, understatement, and paradox, Eminem crafts lyrics that resonate deeply with listeners, offering insights into identity, resilience, and cultural commentary. This analysis underscores Eminem's skill in using figurative language to enrich his storytelling, making his music not only a form of artistic expression but also a potent medium for exploring complex themes in contemporary society. The application of Perrine's theory highlights the effectiveness of figurative language in enhancing lyrical content, while Creswell et al.'s methodological approach ensures a comprehensive and nuanced understanding of the data.